(Co, Mn)3O4 Spinel Coating for Protecting Metallic Interconnects Thermally Converted from an Electro-Codeposited Co-Mn3O4 Composite Coating. (14th August 2018) - Li, Yelong; Song, Jianli; Zhu, Jiahong; Li, Yongtang; Yang, Wen
Abstract : Electro-codeposition was used to prepare the Co and Co-Mn3 O4 precursor coatings on ferritic stainless steel E-brite. Plated samples were exposed at 800°C in air for different durations (i.e., 10 min and 4 h) for thermal conversion of the deposited layer to a spinel coating. The converted layer was characterized with scanning electron microscopy/energy-dispersive spectroscopy (SEM/EDS) and X-ray diffraction (XRD). The results showed that after 10 min heat treatment, the plated Co layer was not fully oxidized and converted into a double-layer microstructure with an inner CoO layer and outer Co3 O4 layer, while for the Co-Mn3 O4 layer, the Mn3 O4 particles were not completely dissolved into the oxide layer. After 4 h of exposure, the surface layer was fully converted into the Co3 O4 or (Co, Mn)3 O4 spinel coating. Though the Mn content in (Co, Mn)3 O4 was relatively low, the Mn-doped spinel coating was advantageous over the pure cobalt spinel coating, as the thermally grown Cr2 O3 scale at the coating/substrate interface was more compact and protective. Co diffusion from the deposited layer into the alloy substrate was observed for both coatings.